Advertisement Remove all ads

Verify :-  x^3 + y^3 = (x + y) (x^2 – xy + y^2) - Mathematics

Verify :-  x3 + y3 = (x + y) (x2 – xy + y2)

Advertisement Remove all ads

Solution

x3 y3 (y)(x2 – xy2)

Wknothat,

(y)3 x3 y3 3xy(y)

⇒ x3 y3 (y)3 – 3xy(y)

⇒ x3 y3 (y)[(y)2 – 3xy]                    Takin(ycommon

⇒ x3 y3 (y)[(x2 y2 2xy– 3xy]

⇒ x3 y3 (y)(x2 y2 – xy)

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 9 Mathematics Textbook
Chapter 2 Polynomials
Exercise 2.5 | Q 9.1 | Page 49
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×